Mechanical unfolding kinetics of the SRV-1 gag-pro mRNA pseudoknot: possible implications for −1 ribosomal frameshifting stimulation - Zhong, Zhensheng (2017)
Minus-one ribosomal frameshifting is a translational recoding mechanism widely utilized by many RNA viruses to generate accurate ratios of structural and catalytic proteins. An RNA pseudoknot structure located in the overlapping region of the gag and pro genes of Simian Retrovirus type 1 (SRV-1) stimulates frameshifting. However, the experimental characterization of SRV-1 pseudoknot (un)folding dynamics and the effect of the base triple formation is lacking. Here, we report the results of our single-molecule nanomanipulation using optical tweezers and theoretical simulation by steered molecular dynamics. Our results directly reveal that the energetic coupling between loop 2 and stem 1 via minor-groove base triple formation enhances the mechanical stability. The terminal base pair in stem 1 (directly in contact with a translating ribosome at the slippery site) also affects the mechanical stability of the pseudoknot. The −1 frameshifting efficiency is positively correlated with the cooperative one-step unfolding force and inversely correlated with the one-step mechanical unfolding rate at zero force. A significantly improved correlation was observed between −1 frameshifting efficiency and unfolding rate at forces of 15–35 pN, consistent with the fact that the ribosome is a force-generating molecular motor with helicase activity. No correlation was observed between thermal stability and −1 frameshifting efficiency.